Three cheers for liberal modesty - Laborde, C (Routledge, 2018)
Many liberals have been immodest in postulating that their own progressive, secular liberalism is the only one that can be justified in public reason. In Liberalism’s Religion, I articulate a more modest theory of liberalism and religion. While I personally endorse progressive secular liberalism, I argue that it is only one of the reasonable conceptions of liberal justice. This liberal modesty has profound, hitherto unnoticed implications for (i) the role of religious arguments in the public sphere, (ii) the legitimacy of religious establishment, and (iii) the justifiability of religious exemptions. In this article, I defend these three claims by providing replies to my critics.